Penyuluhan Kesehatan Telinga dan Pelatihan Cara Merawat Kesehatan Telinga Serta Sosialisasi Perundungan Pada Siswa Sekolah Dasar - Ketut Wahyudiana Sudana; Agus Santosa; I Putu Arwan Puspa Remawan (Warmadewa University Press, 2026)
Ear health problems, such as ear infections and obstructive cerumen, are still frequently found in primary school children and can interfere with learning, language development, and overall quality of life. Meanwhile, bullying in the primary school environment is also a significant problem that affects students’ mental health, self-esteem, and academic achievement. This community service program aimed to improve students’ and teachers’ knowledge and skills regarding proper ear care, while also increasing their understanding of the dangers of bullying and the importance of creating a safe and respectful school environment. The program was implemented at SD Negeri 1 Tonja, Denpasar Utara, one of the public primary schools with a relatively large number of students and located in a densely populated area where cases of obstructive cerumen are still frequently reported according to local primary health care data. The targets of this program were teachers and 38 sixth-grade students. The activities included coordination with the school, ear health education sessions, hands-on training on ear care, and bullying awareness sessions, accompanied by pre–post quizzes, discussions, and educational games. Evaluation was carried out by comparing students’ ability to answer questions before and after the sessions and by observing their engagement during the practical components, followed by brief monitoring through the teachers for three weeks after the program. The results showed that all students attended the entire series of education and training sessions and were able to answer the questions well at the end, indicating an increase in knowledge about ear health and bullying. Students were also able to demonstrate safe ear-cleaning practices and provide examples of behaviors that constitute bullying as well as attitudes that reflect mutual respect at school. Post-program monitoring indicated that students began to apply proper ear care at home and shared the information with their parents, and they became more sensitive in avoiding behaviors that could lead to bullying. This program was effective as an initial step to increase primary school students’ awareness and skills regarding ear health and bullying prevention and has the potential to be replicated in other schools with similar characteristics. Key words: ear health, obstructive cerumen, primary school students, health education, bullying